Learning technologies and the body : integration and implementation in formal and informal learning environments - Lee, Victor R. (Routledge research in education ;, 2015)
This volume explores how technology-supported learning environments can incorporate physical activity and interactive experiences in formal education. It presents cutting-edge research and design work on a new generation of'body-centric'technologies such as wearable body sensors, GPS tracking devices, interactive display surfaces, video game controller devices, and humanlike avatars. Contributors discuss how and why each of these technologies can be used in service of learning within K-12 classrooms and at home, in museums and online. Citing examples of empirical evidence and specific implementation, this timely and critical volume examines how body responsive technologies are being used within the educational community to advance the next generation of educational technology.